Educational Quality Inequality and the Role of Principal Leadership in Realizing Educational Equity - Hasbiyallah, Hasbiyallah; Hermawan, A. Heris; Salsabila, Aulia Nursekha; Nasir, Tatang Muh; Sain, Zohaib Hassan (JURNAL AL-TANZIM, 2026)
Inequality in education is still a structural and ongoing problem in Indonesia. This phenomenon includes regional differences in quality, restricted access to educational technology, and a lack of professional development opportunities for instructors in underprivileged areas. These circumstances have increased the disparity between richer and less developed regions and led to unequal educational services. The purpose of this study is to investigate how school principals may lead in resolving these problems and advancing educational equity. A Systematic Literature Review (SLR) of 34 reputable journal publications and policy papers was used in this investigation. Google Scholar, Scopus, and Garuda were used for the search, and the results were selected based on theoretical contribution, methodological quality, and topic relevance. To identify trends, tactics, and the role of school leadership in advancing educational equity, the data were subjected to thematic analysis. The results show that thoughtful, context-responsive, and participative leadership makes a substantial contribution to closing educational gaps. By encouraging cooperation, raising teacher motivation, and making the most of school resources, principals serve as change agents. The study’s practical implications promote the implementation of equitable national education by highlighting the need for context-specific, long-lasting, and socially just school leadership development strategies.